2021
DOI: 10.3390/molecules26113390
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Seaweed Polysaccharides Stimulating Denitrifying Bacteria for Safer Nitrate Removal

Abstract: Excessive use of nitrogen fertilizer in intensively managed agriculture has resulted in abundant accumulation of nitrate in soil, which limits agriculture sustainability. How to reduce nitrate content is the key to alleviate secondary soil salinization. However, the microorganisms used in soil remediation cause some problems such as weak efficiency and short survival time. In this study, seaweed polysaccharides were used as stimulant to promote the rapid growth and safer nitrate removal of denitrifying bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…E. prolifera has good edible and medicinal values, showing anti-inflammatory and detoxifying effects [27]. E. prolifera contains abundant polysaccharides that exhibit many biological properties, including antioxidant, antiviral, antitumor, anti-inflammatory, immunomodulatory and antibacterial properties [28,29]. In our previous studies, the dietary inclusion of algae (E. prolifera)-derived polysaccharides (ADP) improved the intestinal barrier function of laying hens [30] and broilers [31].…”
Section: Introductionmentioning
confidence: 99%
“…E. prolifera has good edible and medicinal values, showing anti-inflammatory and detoxifying effects [27]. E. prolifera contains abundant polysaccharides that exhibit many biological properties, including antioxidant, antiviral, antitumor, anti-inflammatory, immunomodulatory and antibacterial properties [28,29]. In our previous studies, the dietary inclusion of algae (E. prolifera)-derived polysaccharides (ADP) improved the intestinal barrier function of laying hens [30] and broilers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that high percentage of neral in LVEO exhibits antimicrobial and antioxidant activities ( 19 ). Nevertheless, the antimicrobial activity of neral against several spoilage organisms has been well-documented in in-vitro trials and applied in food storage ( 20 , 21 ). However, some chemically active compounds of EOs are rarely present in food matrices, which have negative impact on the chemical food integrity, physical stableness, and the loss of bioactive activity of bioactive compounds ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…This new strategy of utilizing denitrifying bacteria to safely remediate secondary soil salinization holds significant implications, indicating its active role in the soil nitrogen cycle. This could be achieved by promoting nitrogen release or transformation, including biological processes such as nitrogen fixation and organic matter decomposition [32].…”
Section: Impact Of Atcc6633 Strain On the Growth Physiology Of Rose S...mentioning
confidence: 99%